THE IMPACT OF FACILITIES AND SERVICE QUALITY ON OUTPATIENT SATISFACTION IN THE NERVE POLY, CARDIAC POLY, AND INTERNAL POLY OF RUMAH SAKIT UMUM DAERAH PROF. DR. H. ALOEFI SABOE GORONTALO - Hilumalo, Nurain; Aneta, Asna; Hatu, Rauf (Universitas Negeri Gorontalo, 2020)
This research aims to analyze the impact of facilities and service quality on outpatient satisfaction in the Nerve Poly, Cardiac Poly, and Internal Poly of Rumah Sakit Umum Daerah Prof. Dr. H. Aloei Saboe Gorontalo either partially or simultaneously. The research approach is quantitative. The research method is ex post facto. The research design is causality. The data analysis technique used is double regression. The research findings are that: (1) Service quality has a positive and significant impact on outpatient satisfaction in the Nerve Poly, Cardiac Poly, and Internal Poly of Rumah Sakit Umum Daerah (RSUD) Prof. Dr. H. Aloei Saboe Gorontalo (the coefficient of determination is 43.00%); (2) Facilities have a positive and significant impact on outpatient satisfaction in the Nerve Poly, Cardiac Poly, and Internal Poly of Rumah Sakit Umum Daerah (RSUD) Prof. Dr. H. Aloei Saboe Gorontalo (the coefficient of determination is 12.20%); and (3) Facilities and quality service simultaneously have a positive and significant impact on outpatient satisfaction in the Nerve Poly, Cardiac Poly, and Internal Poly of Rumah Sakit Umum Daerah (RSUD) Prof. Dr. H. Aloei Saboe Gorontalo (the coefficient of determination is 55.20%). Meanwhile, the other 44.80% can be explained by other variables; such as patients’ physiological, psychological, and social factors and health workers and hospital administrative staff’s commitments.